Pengaruh Latihan Shadow Footwork dan Indeks Massa Tubuh terhadap Agility Atlet Bulutangkis Pekanbaru - Ariandi, Jumrah; Nasuka, Nasuka; Kusuma, Donny Wira Yudha (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research was conducted to determine the effect of Shadow footwork training and body mass index on the agility of Pekanbaru Riau badminton athletes. This research uses Quasi Experiment research which is divided into two control groups using a quantitative approach with a 2x2 Factorial design. The population in this study were all male and female athletes from Pb Angkasa and Pb. Bank Riau Kepri, namely 165 people, the sample in this research was 28 male athletes from Bank Riau Kepri, obtained using a purposive sampling technique. The analysis technique used is Two Way ANOVA with the help of the SPSS Statistics 23 application with the prerequisite normality test (Shapiro Wilk test) and homogeneity of variance test (with Levene's test). The results of this research show that 1) a significance value of 0.038 was obtained. The significance value is 0.038 < 0.05, so Ho is rejected and Ha is accepted, which means there is a difference in the effect of shadow training on the agility abilities of Bank Riau Kepri athletes. 2) obtained a significance value of 0.014. The significance value is 0.014 < 0.05, so Ho is rejected and Ha is accepted, which means there is a difference in the influence of body mass index on the agility abilities of Bank Riau Kepri athletes. 3) obtained a significance value of 0.199. The significance value is 0.199 > 0.05, so Ho is accepted and Ha is rejected, which means there is no interaction between the shadow training method and body mass index on the agility abilities of Bank Riau Kepri athletes. Keywords: Agility, Badminton, Body Mass Index Exercise, Shadow Footwork,